2009
DOI: 10.1016/j.neuroscience.2009.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic projections to the medial preoptic area of postpartum rats

Abstract: Dopamine receptor activity in the rodent medial preoptic area (mPOA) is crucial for the display of maternal behaviors, as well as numerous other physiological and behavioral functions. However, the origin of dopaminergic input to the mPOA has not been identified through neuroanatomical tracing. To accomplish this, the retrograde tracer Fluorogold was iontophoretically applied to the mPOA of postpartum laboratory rats, and dual-label immunocytochemistry for Fluorogold and tyrosine hydroxylase later performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 125 publications
(153 reference statements)
0
36
0
Order By: Relevance
“…1, lower row, arrowhead). These cell bodies imply a local source of THpositive processes, although external sources, as reported in mammals (Miller and Lonstein, 2009), may contribute. Our findings agree with previous reports of direct contact between dopaminergic terminals and GnRH1 cells in mammals (Jennes et al, 1983;Lehman et al, 1988;Leranth et al, 1988;Pompolo et al, 2003;Tillet et al, 1989).…”
Section: Resultsmentioning
confidence: 77%
“…1, lower row, arrowhead). These cell bodies imply a local source of THpositive processes, although external sources, as reported in mammals (Miller and Lonstein, 2009), may contribute. Our findings agree with previous reports of direct contact between dopaminergic terminals and GnRH1 cells in mammals (Jennes et al, 1983;Lehman et al, 1988;Leranth et al, 1988;Pompolo et al, 2003;Tillet et al, 1989).…”
Section: Resultsmentioning
confidence: 77%
“…FG and TH immunohistochemistry was performed on every other section throughout the brain using methods similar to previous work from our laboratory [Miller and Lonstein, 2009]. Sections were rinsed with TBS between incubations.…”
Section: Tissue Collection and Immunohistochemistrymentioning
confidence: 99%
“…In all sites, TH-ir cells were examined in every other section through the brain. Previous work in our laboratory demonstrated that confocal analysis of fluorescing secondary antisera was unfeasible because these brain sites are spread throughout the forebrain and midbrain, and the majority of fluorescence was lost before thorough scanning could be completed [Miller and Lonstein, 2009]. To estimate the total number of double-labeled cells in each site, the number of double-labeled cells counted was multiplied by two for each subject, and an Abercrombie correction factor of 0.78 was applied [Abercrombie, 1946].…”
Section: Microscope Analysis Of Fg-labeled Cellsmentioning
confidence: 99%
“…Thus, the presence of HSF1 in dopamine-containing hypothalamic regions was analysed by co-labelling with TH, the rate-limiting enzyme in dopamine synthesis. The POA receives dopaminergic input from other brain regions including the POA/MPA itself [39]. In the POA, HSF1 is co-localised with TH, suggesting a potential role of HSF1 in autoregulatory dopaminergic temperature regulation.…”
Section: Discussionmentioning
confidence: 99%